2014
DOI: 10.18632/oncotarget.2161
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic Effects of PCP4/PEP19 in Human Breast Cancer Cell Lines: A Novel Oncotarget

Abstract: The PCP4/PEP19 is a calmodulin-binding anti-apoptotic peptide in neural cells but its potential role in human cancer has largely been unknown. We investigated the expression of PCP4/PEP19 in human breast cancer cell lines MCF-7, SK-BR-3, and MDA-MB-231 cells, and found that estrogen receptor (ER)-positive MCF-7 and ER-negative SK-BR-3 cells expressed PCP4/PEP19. In the MCF-7 cells, cell proliferation was estrogen-dependent, and PCP4/PEP19 expression was induced by estrogen. In both cell lines, PCP4/PEP19 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 39 publications
6
30
0
Order By: Relevance
“…Loss of Bmi-1 has been reported to inhibit cell proliferation and enhance apoptotic cell death, which decreases Akt phosphorylation in MCF-7 cell [31]. Taken together with our previous results demonstrating that phosphorylation of Akt is reduced by PCP4/PEP19 knockdown [16], our current findings implicate PCP4/PEP19 as a novel factor in the upregulation of EMT in human breast cancer. In addition, the expression of both PCP4/PEP19 and Snail was inhibited by Bmi-1 knockdown, suggesting that PCP4/PEP19 acts downstream of the Bmi-1 signaling pathway in MCF-7 cells but not in T47D cells.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Loss of Bmi-1 has been reported to inhibit cell proliferation and enhance apoptotic cell death, which decreases Akt phosphorylation in MCF-7 cell [31]. Taken together with our previous results demonstrating that phosphorylation of Akt is reduced by PCP4/PEP19 knockdown [16], our current findings implicate PCP4/PEP19 as a novel factor in the upregulation of EMT in human breast cancer. In addition, the expression of both PCP4/PEP19 and Snail was inhibited by Bmi-1 knockdown, suggesting that PCP4/PEP19 acts downstream of the Bmi-1 signaling pathway in MCF-7 cells but not in T47D cells.…”
Section: Discussionsupporting
confidence: 86%
“…PCP4/PEP19 has an anti-apoptotic function in human breast cancer cell lines [16]. In the present study, we demonstrated that loss of PCP4/PEP19 expression decreased cell adhesion, migration, and invasion in MCF-7 and T47D human breast cancer cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…While, the adipocytokine signaling pathway was enriched and predicted to be linked to the expression of multiple genes associated with super-enhancers in the MCF-7 model, STAT3 was not predicted to be associated with any of the super-enhancers in MCF7 compared to the MDA-MB-468 triple negative model; STAT3 was associated with all. Among the top scoring genes associated with the network pathway analysis in MDA-MB-468, unsurprisingly, most genes were associated with promotion of invasion, survival and aggressiveness [205][206][207][208][209][210][211][212][213] relative to those associated with the entire pathway activation in MCF-7 associated with inhibition of tumour suppression and [214,215], promotion of tumourigenesis, migration and survival [216][217][218][219][220][221][222][223]. Comparative downstream pathway analysis of the effect of the adipocytokine pathway in breast cancer using the SEanalysis web tool [224,225] for super enhancer associated regulatory analysis.…”
Section: Adipose Tissue: An Inflammatory Macroenvironment Stimulatingmentioning
confidence: 99%